The HLA‐DRB1*11:23:02 allele confirmed in a Chinese individual by next‐generation sequencing. (29th October 2020) - Zhou, Dan; Zou, Hong‐Yan
Abstract : DRB1*11:23:02 differs from DRB1*11:23:01 by one nucleotide change at nucleotide 357 in exon 2 from G to A.